Unpublished Pontic stories: Collected by R.W.Dawkins - Mackridge, Peter (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1990)
A boy was going to get married. His mother went to the prospective bride’s parents with another woman and the woman’s son. The woman instructed her son to say twice as much as whatever she said. The woman began singing the praises of the prospective bridegroom, saying, «This woman’s boy’s got land worth £200.» «No,» said her son, «£400.» «He’s got a hundred head of sheep.» «No,» said her son, «two hundred.» Then the woman said, «He’s got one defect: he squints in one eye.» «No,» said the son, «both eyes.» Whereupon the father of the prospective bride sent them packing.